Proyeksi Masyarakat 5.0 Melalui Model Pembelajaran Berlandaskan Hots Di Perguruan Tinggi - Wijayanti Wijayanti; Susi Yunarti; Dian Harmaningsih (Universitas Persada Indonesia YAI, 2022)
Writing this research article aims to explain the need to developlearning models and methods based on HOTS in higher education, in orderthey can really contribute positively to the development of society 5.0. Theresearch method is descriptive analytical by conducting observations andinterviews with 30 students at two universities in Jakarta. The results of thestudy show that there was a contradiction between the necessity to carry outonline learning which requires students' digital skills to be further developed,and the need for HOTS development in the learning process. Digitalcapabilities that are a requirement for human quality in the industrial era 4.0must still be equipped with the ability to think, which is problem solving,critical, creatives and innovative. For the future can projection society 5.0.